Performing Arts as a Medium for Teaching Islamic Education in Surabaya - Ilham Hermawan; Nabila Aulia Oliviatika; Zahra Oktaviana Syifa Ramadhan (Indonesian Journal of Islamic Religion and Culture, 2025)
Performing arts in Indonesia are significant in teaching and disseminating Islamic teachings. Through various forms of art, such as theater, music, dance, and puppetry, Islamic values can be conveyed in an engaging and easily understood manner by the community. This article aims to analyze the role of performing arts as a medium for Islamic education and explore the implementation of performing arts in the modern era within Islamic education, particularly in East Java, focusing on Surabaya. Traditional performing arts, such as ludruk, are among Surabaya's most common forms. Additionally, other implementations of performing arts include the establishment of vocational high schools specializing in arts, ranging from traditional to modern. Surabaya also boasts cultural facilities, such as the Cak Durasim Arts Building, which frequently hosts various performing arts events. These activities hold significant potential to serve as a medium for teaching and imparting Islamic values in Surabaya